2018
DOI: 10.1177/2325967118775061
|View full text |Cite
|
Sign up to set email alerts
|

Repair Integrity in Patients Returning for an Unscheduled Visit After Arthroscopic Rotator Cuff Repair: Retorn or Not?

Abstract: Background:After rotator cuff repair, some patients have ongoing problems significant enough to warrant presentation to a clinic for reassessment.Purpose/Hypothesis:The purpose of this study was to determine whether this cohort of patients was more likely to have a healed rotator cuff. We hypothesized that patients who had an unscheduled postoperative visit were more likely to have a healed rotator cuff than those who did not have an unscheduled postoperative visit.Study Design:Cohort study; Level of evidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, multiple studies have shown that for small and medium size tears the re-tear rate is low and does not affect patient reported clinical outcomes. 27 Thirdly, this study had few tears fixed with this technique which were greater than 2 cm overall. Additionally, only survey follow-up was obtained on patients after a minimum of 5 years post-operatively, which limits analysis.…”
Section: Discussionmentioning
confidence: 95%
“…However, multiple studies have shown that for small and medium size tears the re-tear rate is low and does not affect patient reported clinical outcomes. 27 Thirdly, this study had few tears fixed with this technique which were greater than 2 cm overall. Additionally, only survey follow-up was obtained on patients after a minimum of 5 years post-operatively, which limits analysis.…”
Section: Discussionmentioning
confidence: 95%
“…We excluded two recent studies including patients with revision repairs or nonoperative treatment. 5 , 24 Screening of the titles and abstracts of cited and citing references of included records and 18 topical records 7 , 8 , 9 , 15 , 23 , 24 , 26 , 30 , 35 , 40 , 42 , 55 , 58 , 60 , 70 , 71 , 72 , 73 did not yield any additional studies that met our inclusion criteria. A full description of included studies (studied population, outcomes, statistical analyses, and reported effect estimates) is available in Supplemental Tables 1-3 .…”
Section: Resultsmentioning
confidence: 99%